Applied Mechanics / Third Edition - Hannah J; Hillier M. J (Longman Scientific and Technical, 1995)
The essential guide to the basic principles of applied mechanics for all students of engineering. Preface, Statics, Frameworks, Friction, Velocity and Acceleration, Inertia and Change of Motion, Motion in a Circle, Balancing, Periodic Motion, Dynamics of Rotation, Work and Energy and Power, Impulse and Momentum, Aircraft and Rockets, Direct Stress and Strain, Mechanical Properties of Materials, Shear and Torsion, Shear Force and Bending Moment, Bending of Beams, Cimbined Bending and Direct Stress, Fluid at Rest, Fluid in Motion, Experimental Errors and the Adjustment of Data, Index.